Clinical Research Primer for Medical Students: Overview and Illustrative Experiences - Evans, Alexander R.; Stephens, Tressie; Jea, Andrew H.; Bauer, Andrew M.; Dunn, Ian F.; Graffeo, Christopher S. (Journal of Neurological Surgery Reports, 2024)
Background The ability to participate in clinical scholarship is a foundational component of modern evidence-based medical practice, empowering improvement across essentially every aspect of clinical care. In tandem, the need for comprehensive exposure to clinical research has been identified as a critical component of medical student training and preparation for residency that is underserved by traditional undergraduate medical education models. The goal of the current work was to provide guidelines and recommendations to assist novice medical students in taking ownership of their research education.Methods The Clinical Research Primer was composed from pooled research documents compiled by the study authors and our institutional neurosurgery student research group. The Primer was then structured as the natural evolution of a research project from its inception through the submission process.Results We divided the foundational components of the Clinical Research Primer into seven domains, each representing a landmark in the development of a peer-reviewed study, and a set of skills critical for junior scholars to develop. These vital components included the following: pitching and designing clinical studies, developing a research workflow, navigating the Institutional Review Board, data collection and analysis, manuscript writing and editing, submission mechanics, and tracking research projects for career development.Conclusion We anticipate that the tools included in the Clinical Research Primer will increase student research productivity and preparedness for residency. Although our recommendations are informed by our experiences within neurosurgery, they have been written in a manner that should generalize to almost any field of clinical study.
Keywords: research; education; medical student; UME; USMLE